Job morale of physicians in low-income and middle-income countries: a systematic literature review of qualitative studies. Issue 12 (3rd December 2019) - Sabitova, Alina; Sajun, Sana Zehra; Nicholson, Sandra; Mosler, Franziska; Priebe, Stefan
Abstract : Objectives: To systematically review the available literature on physicians' and dentists' experiences influencing job motivation, job satisfaction, burnout, well-being and symptoms of depression as indicators of job morale in low-income and middle-income countries. Design: The review was reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for studies evaluating outcomes of interest using qualitative methods. The framework method was used to analyse and integrate review findings. Data sources: A primary search of electronic databases was performed by using a combination of search terms related to the following areas of interest: 'morale', 'physicians and dentists' and 'low-income and middle-income countries'. A secondary search of the grey literature was conducted in addition to checking the reference list of included studies and review papers. Results: Ten papers representing 10 different studies and involving 581 participants across seven low-income and middle-income countries met the inclusion criteria for the review. However, none of the studies focused on dentists' experiences was included. An analytical framework including four main categories was developed: work environment (physical and social), rewards (financial, non-financial and social respect), work content (workload, nature of work, job security/stability and safety), managerial context (staffing levels, protocols and guidelines consistency and political interference). The job morale of physicians working in low-income and middle-income countries was mainly influenced by negative experiences. Increasing salaries, offering opportunities for career and professional development, improving the physical and social working environment, implementing clear professional guidelines and protocols and tackling healthcare staff shortage may influence physicians' job morale positively. Conclusions: There were a limited number of studies and a great degree of heterogeneity of evidence. Further research is recommended to assist in scrutinising context-specific issues and ways of addressing them to maximise their utility. PROSPERO registration number: CRD42017082579.